Immunoglobulin A Nephropathy. Recurrence After Renal Transplantation - Moroni, Gabriella; Belingheri, Mirco; Frontini, Giulia; Tamborini, Francesco; Messa, Piergiorgio (Frontiers in Immunology, 2019)
IgA nephropathy (IgAN) is the most common primary glomerular disease worldwide. It is characterized by dominant or co-dominant diffuse mesangial deposition of IgA, which, in most cases, are aberrantly glycosylated. The disease generally runs an indolent course but may lead to ESRD in 30% to 50% of patients in 20 years or more after diagnosis. Patients with IgA nephropathy are ideal candidates for renal transplant, because they are generally relatively young and with few comorbidities. Survival of IgA transplanted recipients is not different from that of those transplanted for other glomerular diseases. Graft survival is better than that of controls during the first 5 years of renal transplant, it is comparable at 10 years, but becomes worse with prolongation of observation. Worse outcome is partly attributed to disease recurrence that is particularly frequent in IgAN. Owing to progressive improvement of graft survival, resulting from reduced incidence of acute rejection, the number of patients potentially exposed to recurrence has increased. Recurrences of IgAN can be “histological only” when diagnosed on protocol biopsies in asymptomatic patients; or “clinical,” when associated with urinary abnormalities and/or graft dysfunction. Recurrent IgAN rarely manifests clinically before 5 years post transplantation. Recurrence rate is estimated to range around 30%. However, recurrence rate varies greatly among different centers because of the differences both in policy of graft biopsy and follow-up duration. Despite there is no certain recurrence predictor, young age at renal transplant, rapid progression of the original disease and higher levels of circulating galactose-deficient IgA1 and IgA-IgG immune complexes are all associated with higher rate of recurrence. It is unknown if recurrence is more frequent in recipients from living donors in comparison to recipients from deceased donors. There is no proven specific therapy for recurrent IgA. However, some retrospective data suggest that the rate of recurrence is higher in patients in whom steroids were withdrawn. The aim of this review is to describe the clinical outcome of renal transplantation in IgA patients with attention to the rate and the predictors of recurrence and to discuss the available therapeutic options for the management of recurrence.